Embodied Virtual Patients as a Simulation-Based Framework for Training Clinician-Patient Communication Skills: An Overview of Their Use in Psychiatric and Geriatric Care - Chaby, Laurence; Benamara, Amine; Pino, Maribel; Prigent, Elise; Ravenet, Brian; Martin, Jean-Claude; Vanderstichel, Hélène; Becerril-Ortega, Raquel; Rigaud, Anne-Sophie; Chetouani, Mohamed (Frontiers in Virtual Reality, 2022)
Clinician-patient communication is essential to successful care and treatment. However, health training programs do not provide sufficient clinical exposure to practice communication skills that are pivotal when interacting with patients exhibiting mental health or age-related disorders. Recently, virtual reality has been used to develop simulation and training tools, in particular through embodied virtual patients (VP) offering the opportunity to engage in face-to-face human-like interactions. In this article, we overview recent developments in the literature on the use of VP-simulation tools for training communicative skills in psychiatry and geriatrics, fields in which patients have challenging social communication difficulties. We begin by highlighting the importance of verbal and nonverbal communication, arguing that clinical interactions are an interpersonal process where the patient’s and the clinician’s behavior mutually shape each other and are central to the therapeutic alliance. We also highlight the different simulation tools available to train healthcare professionals to interact with patients. Then, after clarifying what communication with a VP is about, we propose an overview of the most significant VP applications to highlight: (i) in what context and for what purpose VP simulation tools are used in psychiatry (e.g. depression, suicide risk, PTSD) and geriatrics (e.g., care needs, dementia), (ii) how VP are conceptualized, (iii) how trainee behaviors are assessed. We complete this overview with the presentation of VirtuAlz, our tool designed to train health care professionals in the social skills required to interact with patients with dementia. Lastly, we propose recommendations, best practices and uses for the design, conduct, and evaluation of VP training sessions